Modeling Reliability in Freeway Networks. Issue 1 (January 2014) - Wu, Ning; Geistefeldt, Justin
The stochastic nature of freeway capacity typically has been analyzed at specific points that are considered bottlenecks. The stochastic relationship between the adjacent bottlenecks has not been taken into account. This paper introduces a concept for the stochastic interpretation of capacity and breakdown probability within a larger freeway network consisting of several combined bottlenecks. The presented stochastic methodology delivers a theoretical average capacity and the probability of breakdown for freeway segments of different lengths. The methodology can also be used to identify the effects of consecutive freeway segments and bottlenecks such as on-ramps, off-ramps, and weaving areas having different characteristics. The proposed method makes it possible to determine the breakdown probability as a function of the average volume or density. Hence, the risk of traffic flow disturbance along a freeway segment or within a freeway network can be analyzed.